Strategic State Governance: Synergy Aspect of the National Goals Identification - Grebliauskas, Artūras (Ekonomika, 2002)
Тhe article analysis through the prism of synergy terms the system of state goals: their structure, composition, hierarchy and interrelationship. Three positive levels of goals are distinguished: mega, macro and micro. Important role in the article is added to the concept of the bifurcation point in the sense that the bifurcation point is аt а macro level which marks the change in quality. The article also defines synergy terms: two related to being and five - to transformation that are used in the analysis of state goals.